Lung Transplantation Evolving Knowledge and New Horizons (Springer International Publishing, 2018)
This book details all aspects of lung transplantation and equips the general pulmonologist/physician with the necessary tools and knowledge to assist patients with the preparation for and care post lung transplantation. Written by global experts, chapters present general principles and history; indications and eligibility for lung transplantation, including screening for COPD, cystic fibrosis, scleroderma, Idiopathic pulmonary fibrosis (IPF) and idiopathic pulmonary arterial hypertension; approach to and complications of lung transplantation, such as prognostic markers, radiological approach, and immunology and rejection; and medical and surgical guidelines for lung transplantation. The goal of lung transplantation is to increase survival and to provide a greater quality of life for patients with untreatable end-stage lung disease and this book serves to best prepare clinicians in achieving that goal. Lung Transplantation: Evolving knowledge and New horizons offers valuable insights into this modality and is an authoritative resource for multidisciplinary services that include experts in pulmonary diseases, critical care, cardiology, thoracic surgery, infection diseases, internal medicine , radiology , immunology, nephrology, rehabilitation, psychology /psychiatry , nurses, social workers and nutritionists.